Patients with Pediatric Obstructive Sleep Apnea Show Altered T-Cell Populations with a Dominant TH17 Profile. (May 2014) - Anderson, Martin E.; Buchwald, Zachary S.; Ko, Je; Aurora, Rajeev; Sanford, Thomas
Objective: To characterize the immunologic changes of the tonsil as they correlate with increasing apnea-hypopnea index (AHI) in children. Study Design: Prospective immunologic analysis. Setting: Tertiary care pediatric otolaryngology practice. Subjects: Tonsils were collected from 24 children with obstructive sleep apnea, all of whom had undergone polysomnography at an accredited sleep center using scoring determined by the American Academy of Sleep Medicine 2007 scoring manual. Patients were excluded if they had been diagnosed with craniofacial abnormalities, neuromuscular disorders, or immunodeficiency. Methods: Single-cell suspensions were isolated from tonsils of 13 individuals and stained with fluor-conjugated antibodies and analyzed using fluorescence-activated cell sorting. Single-cell suspensions from tonsils of 11 additional individuals were incubated 21 hours and subjected to multiplexed enzyme-linked immunosorbent assay cytokine analysis. Results: In patients with an AHI >5 events/h, there was a statistically significant increase in the fraction of CD4 + CD45RO + T cells ( P < .01), and the percentage of CD8 + FoxP3 + T cells (TcREG ) showed a statistically significant decrease ( P < .005). Cytokine analysis revealed high levels of interleukin (IL)–17A, IL-1b, IL-10, and IL-12p70 production. Cytokine profiles revealed a conspicuous absence of IL-4 and IL-2. Conclusions: Our results indicate the tonsils of patients with obstructive sleep apnea have an ongoing inflammatory response characterized by increased effector CD4 T cells and decreased FoxP3 CD8 T cells. The TH 17 skewing suggests that local immune activation may be either autoimmune or due to an extracellular pathogen.